2015
DOI: 10.1073/pnas.1516057112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cyclic AMP/protein kinase A- and glucocorticoid-mediated apoptosis using S49 lymphoma cells as a model system

Abstract: Cyclic AMP/protein kinase A (cAMP/PKA) and glucocorticoids promote the death of many cell types, including cells of hematopoietic origin. In wild-type (WT) S49 T-lymphoma cells, signaling by cAMP and glucocorticoids converges on the induction of the proapoptotic B-cell lymphoma-family protein Bim to produce mitochondria-dependent apoptosis. Kin–, a clonal variant of WT S49 cells, lacks PKA catalytic (PKA-Cα) activity and is resistant to cAMP-mediated apoptosis. Using sorbitol density gradient fractionation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…On the other hand, substantial evidence indicates that pro-apoptotic events of cAMP in nucleated cells are, at least in part, mediated by the PKA-dependent phosphorylation of protein targets. 61 , 62 Given that the effects of ABT-737, TQ, and PKA on nucleated cell apoptosis partially involve regulation of gene expression, it is difficult to compare these findings to the situation in platelets. For example, in Jurkat T-cells, TQ downregulated the expression of phosphodiesterases PDE1, PDE3, and PDE4 during 24 h of incubation, which increased cGMP levels and reduced cAMP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, substantial evidence indicates that pro-apoptotic events of cAMP in nucleated cells are, at least in part, mediated by the PKA-dependent phosphorylation of protein targets. 61 , 62 Given that the effects of ABT-737, TQ, and PKA on nucleated cell apoptosis partially involve regulation of gene expression, it is difficult to compare these findings to the situation in platelets. For example, in Jurkat T-cells, TQ downregulated the expression of phosphodiesterases PDE1, PDE3, and PDE4 during 24 h of incubation, which increased cGMP levels and reduced cAMP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…on the association between PKA regulatory subunits and putative signaling effectors. These include RII␤ interacting with G␣ i in response to the coincident activation of G i -and G s -coupled receptors, enhancing MAPK signaling (20), and RI␣ interacting with Bim (B-cell lymphoma family protein), contributing to mitochondria-dependent apoptosis in S49 cells, also involving PKA catalytic activity (21). Consistent with a model in which RI␣ interacts with P-REX1 and acquires an active conformation that promotes P-REX1 activity, we found that RI␣ mutants with alterations at their CNB-B domain actually exhibited a better interaction with P-REX1 than WT RI␣.…”
Section: Camp Activates P-rex1 Via Type I Pka Regulatory Subunitsmentioning
confidence: 99%
“…PKA activity is regulated by intracellular concentration of cAMP, which is determined by the balance between synthesis and degradation by adenylate cyclase (12) and phosphodiesterases (13), respectively. Both proapoptotic and antiapoptotic effects of PKA were reported in nucleated cells (14,15). PKA is highly expressed, and PKA activity is strictly balanced in platelets (16,17).…”
Section: Introductionmentioning
confidence: 99%